Web小説における人気作品群の物語進行に伴う感情変化の定量的解析 - 深澤 佑介; 渡邉 真 (人工知能学会論文誌, 2025)
In this study, we clarify the differences in emotional characteristics and their temporal changes in the narrativesof popular and general web novels. We collect text data from the Shousetsuka ni Narou website, define the top 300works in the global point ranking as popular works, and randomly select another 300 works as general works. Toperform sentiment analysis at the sentence level, we fine-tune a pre-trained Japanese BERT model using the WRIMEdataset for emotion analysis, classify each sentence into Plutchik ’s eight basic emotions (joy, sadness, anticipation,surprise, anger, fear, disgust, and trust), and extract an 8-dimensional emotion score for each sentence. We dividethe text into fixed-length segments, calculate the average emotion scores as features, construct a classification modelusing Random Forest, and clarify differences in emotional tendencies through SHAP analysis. As a result, we showthat differences in emotional characteristics and their temporal changes in narratives significantly influence a work’spopularity. In the early stages of narratives, anticipation contributes positively to popularity, while surprise and fearcontribute negatively. This suggests that instead of evoking surprise or fear regarding the protagonist’s problems,inducing empathy and a sense of anticipation for their resolution is important for attracting readers emotionally. Inthe middle stages, we find that the development of trust among characters serves as preparation for challenges in thelatter part of the story, playing an important role in the emotional flow of popular works. In the final stages, we observethat popular works maintain emotions related to anticipation and trust as the narrative progresses, while emotions suchas surprise and fear decrease. This suggests that in popular works, strengthening the trust relationship between theprotagonist and companions forms the foundation of the narrative and promotes readers’ emotional immersion.